Did hydroxychloroquine played crucial role as prophylactic drug against SARS-CoV-2 infection in resource-constrained and overloaded health care systems in countries like India: a prospective multicentre study in dedicated COVID hospitals - Dalal, Dhaval; Govindwar, Ankush; Gangwani, Gaurav; Dalal, Komal; Nipane, Humeshwari; Gawali, Vijaykumar (International Journal of Advances in Medicine, 2020)
Background: The Indian council medical research (ICMR) recommended to use hydroxychloroquine (HCQ) as a prophylactic agent against Severe acute respiratory syndrome coronavirus-2019 (SARS-COV-2) infection to cater need to protect high-risk individuals considering its pre-clinical data. This study explores role of HCQ in health care workers serving in coronavirus-2019 (COVID-19) pandemic. Methods: The study was planned as multi center observational study, conducted from April, 2020 to August 2020 at COVID-19 hospitals in India. HCQ 400 mg twice a day on day-1 followed by 400 mg once weekly for next 7 weeks was administered to Health care workers (HCW). RTPCR test was conducted at 3 months post last dose of prophylaxis in symptomatic health care workers. IgG test was conducted in all participants at 3 months. Results: We enrolled 1310 asymptotic frontline healthcare workers, of which 585 (45%) were male and 725 (55%) were female. Chi-Sqaure test statistical analysis in RTPCR Test showed p=0.515, p=0.634, p=0.00 in doctor and nurse, housekeeping and other staff respectively. Chi-Sqaure test statistical analysis in IgG antibody tests showed p=0.305, p=0.449 and p=o.345 in doctor and Nurse, Housekeeping and Other staff respectively. Conclusions: HCQ did not provide statistically significant pre exposure prophylaxis to doctors, nurses and housekeeping staff. However for, “other staff members category” it showed highly statistically significant prophylaxis effect with respect to RTPCR positive test results in comparison with HCW who did not consume HCQ prophylaxis. And hence HCQ could certainly play a crucial role in resource-constrained and overloaded health care systems in countries like India.